2018
DOI: 10.1101/484436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alternative Promoters Drive Human Cytomegalovirus Reactivation from Latency

Abstract: Reactivation from latency requires reinitiation of viral gene expression and culminates in the production of infectious progeny. The major immediate early promoter (MIEP) of human cytomegalovirus (HCMV) drives the expression of crucial lytic cycle transactivators but is silenced during latency in hematopoietic progenitor cells (HPCs). Because the MIEP is poorly active in HPCs, it is unclear how viral transactivators are expressed during reactivation. We demonstrate that transcripts originating from alternative… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(61 citation statements)
references
References 25 publications
9
52
0
Order By: Relevance
“…4B) transcription. These findings are consistent with previous findings using the THP-1 culture system (16). However, AP-1 mut p -infected Kasumi-3 cells displayed impaired MIEP-, iP2-, and dP-derived transcripts compared to cultures infected with either WT or AP-1 rep (Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…4B) transcription. These findings are consistent with previous findings using the THP-1 culture system (16). However, AP-1 mut p -infected Kasumi-3 cells displayed impaired MIEP-, iP2-, and dP-derived transcripts compared to cultures infected with either WT or AP-1 rep (Fig.…”
Section: Resultssupporting
confidence: 93%
“…While these alternative transcripts differ in their 5’UTR, each encodes full-length IE1 or IE2 protein (15). More recently, Collins-McMillen et al found two of these alternative transcripts derived from promoters within intron A, iP1 and iP2, are important for reactivation from latency (16). However, the contribution of transcription factor binding on the activity of these alternative promoters during reactivation is unknown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However we recently discovered two alternative promoters (iP1 and iP2, together referred to as intronic promoters) within the first intron of the canonical major immediate early locus(9). Rather than inducing MIEP activity, HCMV reactivation stimuli instead induce transcription from the iP1 and iP2 promoters, which correlates with the increase in IE1 and IE2 mRNA levels(10). Deletion of the intronic promoters significantly attenuates the production of infectious virus after reactivation, revealing that the iP1 and iP2 promoters play critical roles in IE1 and IE2 re-expression and HCMV reactivation.…”
Section: Introductionmentioning
confidence: 99%